Development of Learning Media Based on Google Sites with a Problem-Based Learning Approach to Increase Interest in Learning Data Communication and Computer Networks - Shava Aulia, Xaphyra Aura; Al Idrus, Shofiyah; Asfani, Khoirudin (Letters in Information Technology Education (LITE), 2024)
This research and development aims to develop learning media that can provide new learning resources to students, support the learning process of theory and practicum, overcome material that students find difficult, create an independent atmosphere in learning, and increase student interest in learning. This research and development methodology uses the R&D (Research & Development) method with the 5D development model developed by Pranata in 2009, which has five complex stages, namely: (1) define, (2) data collection, (3) design, (4) develop, and (5) disseminate. This learning media was tested by media experts, material experts, and users who are undergraduate students of Informatics Engineering Education who have taken data communication and computer network courses at the State University of Malang. This research and development produce quantitative and qualitative data using data collection techniques such as observation, interviews, and distributing questionnaires. The results of this research and development can be concluded that: (1) the validity and reliability test of the instrument as many as 30 question items have a value of r count> from r table, which can be declared valid and obtain a reliability value of 0.948 with a reliable or powerful instrument category, (2) media experts obtained a total score of 86 per cent with very valid assessment criteria, (3) material experts obtained a total score of 96 per cent with very valid assessment criteria, (4) limited trials obtained a total score of 88 per cent with very valid assessment criteria, (5) field trials obtained a total score of 86 per cent with very feasible assessment criteria and (6) learning interest obtained a total score of 85 per cent with a very good assessment category